Pengaruh Gambir (Uncaria gambir R.) Terhadap Penyembuhan Luka Bakar Pada Mencit Putih (Mus musculus L.) Jantan - Nelsy Sucidayana Sumosa; - Efrizal; Resti Rahayu (Jurnal Biologi Universitas Andalas, 2014)
An experimental study on the effect of Gambier (Uncaria gambir R.) on burned skin of male white mice (Mus musculus L.) was conducted at The Animal Physiology Laboratory Andalas University. This experiment used Complete Random Design (CDR) consisted of five treatments, i.e: 0.00%, 0.25%, 0.50%, 0.75%, 1.00% and five replication with the observation lasted for 15 days. The results showed that Gambier gave significantly different effects (p = 0.004) on both the percentage of healing and the wound recovery. The highest percentage of wound healing was 94.783% and the largest diameter of wound recovery was 9.436 mm obtained at 0.50%  at 8 days.Keyword: Uncaria gambir, burned skin, wound recovery.